Systemic Functional Linguistics and Discourse Analysis as Alternatives When Dealing With Texts - Paula Andrea García Montes; Ana María Sagre Barboza; Alba Isabel Lacharme Olascoaga (Universidad Nacional de Colombia, 2014)
This article presents a case study research with aims to find out which activities, methodological and textual aspects used in a reading strategies course were causing a group of students difficulties when analyzing critically written information. We conducted the study at Universidad de Córdoba (Colombia) with seventh semester students from the undergraduate English program. The data collection techniques used included observations, document analysis, interviews, and a Preliminary English Test for students. The results were analyzed taking into account issues in discourse analysis and systemic functional linguistics. Results show reasons why students find it difficult to successfully complete the analysis of written texts. These results can serve as useful alternatives for planning reading lessons.